Dynamic Access Control Model for Security Client Services in Smart Grid - Sang-Soo Yeo; Si-Jung Kim; Do-Eun Cho (International Journal of Distributed Sensor Networks)
In the next-generation intelligent power grid, known as the smart grid, various objects can access systems in several network environments, and, accordingly, access control security becomes critical. Thus, to provide users with secure services in the smart grid, a new access control security model is needed. This paper proposes a dynamic access model for secure user services in the smart grid environment. The proposed model analyzes the user's various access contexts and chooses an appropriate context type among the predefined context types. And then it applies the context-based user security policy to allow the user's access to services dynamically. Therefore, it provides stronger security services by permitting context information-applied security services and flexible access control in various network environments. It is expected that this study will be used to solve important access control issues when establishing the smart grid.